Effect of Anchovy Flour Substitution on Tuna Meatballs (Tori meatballs) on Body Weight and Total Protein of Wistar Rats - Lirista Dyah Ayu Oktafiani; Farida Wahyu Ningtyias; Septi Nur Rachmawati; Abdul Azis Akbar; Ruli Bahyu Antika; Septy Handayani; Yunita Satya Pratiwi; Karera Aryatika; Manik Nur Hidayati (Humanistic Network for Science and Technology (HNST), 2022)
Stunting is a growth disorder in children as a result of chronic nutritional problems. This causes the child's height does not match his age. Various efforts have been made to reduce the prevalence of stunting. One of the innovations that can be done is the development of new food products by modifying meatballs derived from tuna with anchovy flour substitution (tori meatballs). This study aims to determine the effect of giving tori meatballs on total protein levels and body weight. The study was conducted for 14 days. The research sample consisted of 27 male wistar rats which were divided into 3 groups, namely K as the control group, P1 as the treatment group with 1 g/day of tori meatball, and P2 the treatment group with 2 g/day of tori meatball. Body weight was measured daily with a digital scale. Total protein assay using Kingsley Method with biuret reagent. The results showed that body weight and total protein content were not statistically different. The provision of tuna meatballs with anchovy flour substitution (tori meatballs) had no effect on body weight and total protein content of wistar white rats. Keywords: stunting; tori meatballs; protein total levels; wistar rats